Reform Responsa Concerning Persons with Disabilities - Abrams, Judith Z. (Journal of religion, disability & health, 2007)
The deciding body on individual questions of Jewish practice, the Responsa Committee of the Central Conference of American Rabbis, has issued many opinions on matters concerning disabilities over the years. This small, but representative, sample shows how the Reform Movement views responsibilities to those with disabilities and the rights of persons with disabilities to participate in Jewish life.